Processing Dry Coconut Sweet in Sindangsari Village, Pangandaran Regency - Apriliana, Arina; Permana, Lutfi Gista; Muhaimin, Muhammad Taufik; Nuranisa, Rifni; Patiniah, Shinta Alvionita; Damayanti, Tsalsa Putri; Muharani, Yesi; Lestari, Asti Tri (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Coconut plant in Indonesia is one of the plants that is very useful in rural economic life, precisely in Sindangsari Village. All parts of the coconut tree can be utulized to meet human needs. This training aims to develop the potential of coconut fruit in the community how to process coconut to become candied dried coconut, to help local people’s income. Residents of Sindangsari Village and a group of PKK women collaborated with UMTAS Group 13 KKN students with the theme “Creative Economy”. This was done to improve and empower the PKK women’s group and also to introduce “Dried Coconut Sweets Processing”. This research was conducted in August – September 2022 in Sindangsari Village, Cimerak District, Pangandaran Regency.